The May 13 generation the Chinese middle schools student movement and Singapore politics in the 1950s - Tan, Jing Quee; Tan, Kok-Chiang; Hong, Lysa (Strategic Information and Research Development Centre, 2011)
This book comprises the recollections penned by the participants of the era of the 1950s, where their generation was in the forefront of the anti-colonial movement, and the work of academic researchers who have examined the historical framework and context of the period, as well as how it has been made to fit into the country's mainstream history. The researchers have also examined the students' cultural expressions, whether it is in art, drama, dance or literature and found them to be socially engaged, and grappling with the question of who they were as a people. The cultural explorations of that period have been forgotten or repudiated. It is revealing just how this amnesia and silence has become so set.